(untitled) (InKoj. Philosophy & Artificial Languages, New series, 2011)
A few months ago, I had two great chances on a single day: I found out and learnt about Silbo, a whistled languagce spoken in a Canary Island, and met Francesca Phillips, ﬁlm maker and photographer, who’s recently written and directed a documentary about it. This article will try to recreate that day - on a small scale and unfortunately silently. In the following pages you will ﬁnd a report of the event, as well as an interview with the director.